Validitas Hukum Perjanjian Clickwrap dan Browsewrap dalam Transaksi E-commerce: Kajian Normatif terhadap Prinsip Konsensualisme - Subarkah, Amirah Dwi; Gravionika, Elsa (Legalita, 2024)
This study is situated within the field of civil law, focusing on the legal validity of clickwrap and browsewrap agreements in e-commerce transactions in Indonesia. The objective is to analyze the conformity of these electronic agreements with the principle of consensualism under national contract law. The topic was chosen due to the increasing use of digital agreements and the absence of comprehensive regulations governing them. The method employed is normative legal research with a juridical-analytical approach to relevant legislation, legal doctrines, and literature. The hypothesis posits that the legal validity of clickwrap and browsewrap agreements faces significant challenges due to misalignment with the principle of consensualism. The main findings indicate the necessity for clearer legal recognition and consumer protection to ensure these agreements function effectively as contractual instruments. This research contributes to strengthening the normative foundation for developing electronic agreement regulations in Indonesia. The results underscore the importance of legal reform to provide legal certainty for stakeholders in the rapidly evolving digital transaction landscape.